Bioactive sulfur-containing compounds from Xanthium sibiricum, including a revision of the structure of xanthiazinone. (May 2020) - Xia, Zhao; Xu, Tian-qi; Zhang, Hai-xin; Chen, Yi-min; Xu, Wei; Zhou, Guang-xiong
Abstract: Seven previously undescribed sulfur-containing compounds, (+)- and (−)-xanthiazinone A, (+)- and (−)-xanthiazinone B, (+)- and (−)-xanthiazinone C and xanthiazinone D, and four known thiazinedione derivatives, together with three thiophene derivatives were isolated from the fruits of Xanthium sibiricum . Racemic xanthiazinones A-C were separated by chiral HPLC columns. Their chemical structures were elucidated based on extensive spectroscopic analyses, ECD calculations, and single crystal X-ray diffractions. The X-ray crystallographic analyses for xanthiazinones A-C represent the first example described for the structure elucidation of the thiazinedione with the five-membered lactone ring attached via an oxygen atom. Accordingly, the previously proposed structure for xanthiazinone was revised. The anti-inflammatory and cytotoxic activities were evaluated for all the isolated compounds. (+)-xanthiazinone B and 2-hydroxy-xanthiazone exhibited potent inhibitory effects against nitric oxide production in lipopolysaccharide-activated RAW 264.7 mouse macrophage cells with IC50 values of 8.75 and 10.90 μM, respectively. All compounds obviously were inactive for three human tumor cell lines (HepG2, MCF-7, and A549) with IC50 values more than 10 μM. Graphical abstract: Seven previously undescribed thiazinedione derivatives together with seven known sulfur-containing compounds were isolated from the fruits of Xanthium sibiricum . Two compounds exhibited potent anti-inflammatory activity. Image 1 Highlights: Seven undescribed xanthiazinones were isolated from the fruits of Xanthium sibiricum. Three pairs of enantiomers were successfully separated by chiral HPLC columns. The previously reported structure for xanthiazinone was revised. (+)-Xanthiazinone B and 2-hydroxy-xanthiazone exhibited potent anti-inflammatory activity.